Sandwich-like MoO3/ZnCo2O4 QDs@C@rGO/MoO3 hybrid nanosheets as high-performance anode for lithium-ion batteries. Issue 22 (15th November 2021) - Liang, Wenfei; Zhong, Linping; Quan, Lijun; Wang, Xuejia; Liu, Mengjiao; Lai, Xin; Bi, Jian; Gao, Daojiang; Liu, Xiaohong; Zhang, Wei; Zhao, Yan
Abstract: Transition metal oxides (TMOs) based compounds are recognized as high-energy anodes in next-generation lithium-ion batteries (LIBs) due to their extremely high theoretical capacity. However, the lower intrinsic conductivity, fast fading cyclic stability and dramatic volume expansion during discharge/charge processes greatly hinder the practical application of TMOs as anodes in LIBs. In this study, we have designed and constructed MoO3 /ZnCo2 O4 QDs@C@rGO/MoO3 (denoted as GMZCO) sandwich-structured hybrid nanocomposites via an effective route, and have proposed the formation mechanism of this unique nanostructured composite on the basis of the systematic results of the microstructures. Due to the unique sandwich structure and the synergistic enhancement effect of the ZnCo2 O4 QDs, α-MoO3 and rGO, the as-constructed GMZCO exhibits the superior electrochemical performances when used as anode for LIBs. The obtained GMZCO can maintain high capacity of 1281 mAh g −1 at 0.2 A g −1 after 300 cycles, and can deliver as high as specific capacity of 913 mAh g −1 at 1 A g −1 after 500 cycles, revealing the higher capacity and excellent cyclic stability. What deserves to be mentioned most is that GMZCO can keep a capacity of 541 mAh g −1 after 1400 cycles even at higher current density of 3 A g −1, having outstanding rate capability. This work paves a novel approach for design TMOs with unique microstructures as a promising anode for the high-performances LIBs.